Novel Keratinolytic Activity of Cyberlindnera fabianii Nrc3 Aza as A Plant Growth Promoting Agent (PGPA) - Abdel-fattah, Azza M.; Nashy, EL-Shahat H. A.; Sabiel, El-Tahir A.; Hussien, Manal M.; Attia, Ahmed S. (International Journal of Applied Sciences and Biotechnology, 2015)
Two field experiments had been conducted in Nubaria sandy soil, Behaira Governate, Egypt to show the effect of keratinase enzyme produced by the novel microbial isolate (Cyberlindnera fabianii NRC3 Aza) on plants.The trials had been conducted in the two successive summer seasons (2011/2012 and 2012/2013) to show the effect of keratinase enzyme from degraded feather–waste on the morphology and chemical composition of peas pods (Pisumsativum L.)–family Fabaceae (Leguminasae). In 2011/2012 season, only the chemical analysis of the dried powdered beads was studied. In 2012/2013 season, the morphological studies of the yield were considered beside the chemical ones. The results depicted significant effects of the sprayed enzyme (keratinase) on peas as plant growth promoting agent (PGPA), compared with the blank (sprayed with water). Electrophoreses and amino acid analysis were carried out for the characterization of the partial pure keratinase enzyme. Int J Appl Sci Biotechnol, Vol 3(4): 609-618